Effects of partial replacement of cotton seed meal for sheep in confinement - an economic analysis - Neto, José de Souza; Gutierrez, Nestor; Costa, Odorico de Moraes Eloy da; Barros, Nelson N. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was to make an economic analysis of the results of partial replacement of cotton seed meal by Christinas bush ("mata-pasto") hay on sheep production in confinement at 0%, 5%, 10% and 15% levels. Costs, income and gross return were analysed. The results showed that all systems had a negative return. The best gross return was obtained when the Christinas bush has replaced the cotton seed meal in 5%.